2021
DOI: 10.1007/s00068-021-01799-6
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatment of fragility fractures of the pelvis: a critical analysis of 140 patients

Abstract: Background Fragility fractures of the pelvis (FFP) are a clinical entity with an increasing frequency. Indications for and type of surgical treatment are still a matter of debate. Purpose This retrospective study presents and critically analyses the results of operative treatment of 140 patients with FFP. Setting Level-I trauma center. Materials and methods Demographic data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…Complications encountered in our patients are similar to those described in the study by Rommens et al, the most frequent being urinary tract infection and bedsores [21]. The complications found in our patients are also comparable to the general population, as the second most common medical condition experienced by geriatric patients is urinary tract infection [22].…”
Section: Safetysupporting
confidence: 89%
See 2 more Smart Citations
“…Complications encountered in our patients are similar to those described in the study by Rommens et al, the most frequent being urinary tract infection and bedsores [21]. The complications found in our patients are also comparable to the general population, as the second most common medical condition experienced by geriatric patients is urinary tract infection [22].…”
Section: Safetysupporting
confidence: 89%
“…Additionally, the length of postoperative hospitalisation was shorter than in comparable studies looking at patients with minimally-invasive procedures, where the median hospitalisation was 12 and 17 days [14,21]. The pain reported by our patients after the operative procedure was less than in similar studies published to date [21].…”
Section: Clinical Outcomescontrasting
confidence: 50%
See 1 more Smart Citation
“…There are several options such as iliosacral screw osteosynthesis, trans-sacral bar osteosynthesis, lumbopelvic fixation, or sacroplasty [8][9][10]. Recent studies showed that percutaneous treatment is associated with fewer complications, shorter length of hospital stay and lower mortality than open surgical techniques [11,12]. Accurate diagnostics in FFP are challenging: in patients with anterior pelvic lesions, involvement of the posterior pelvis is frequently missed [13].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data on the origin, diagnosis, treatment strategy and outcome of FFP become increasingly available, but there still is uncertainty and controversy on how to manage these lesions [6][7][8]. Several authors bring arguments for conservative, others for operative treatment [9][10][11]. Osterhoff et al state that patients with FFP are of old age and present with several comorbidities.…”
Section: Introductionmentioning
confidence: 99%